2011
DOI: 10.2217/fmb.11.116
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Coxiella Burnetii : On the Path of Specialization

Abstract: Coxiella burnetii is an extremely infectious, zoonotic agent that causes Q fever in humans. With the exception of New Zealand, the bacterium is distributed worldwide. Coxiella is classified as a select agent based on its past and potential use as a bioweapon and its threat to public health. Despite decades of research, we know relatively little regarding Coxiella’s molecular pathogenesis, and a vaccine is not widely available. This article briefly reviews the unusual genetics of C. burnetii; a pathogen that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 99 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…Within the macrophage, a high‐density mixture of LCVs and SCVs exists in the parasitophorous vacuole (Minnick and Raghavan ). The LCV is very fragile (Minnick and Raghavan ). While the long survival of C. burnetii infectivity in milk (Combiescu et al .…”
Section: Properties Of the Coxiella Burnetii Organism With Relevance mentioning
confidence: 99%
See 2 more Smart Citations
“…Within the macrophage, a high‐density mixture of LCVs and SCVs exists in the parasitophorous vacuole (Minnick and Raghavan ). The LCV is very fragile (Minnick and Raghavan ). While the long survival of C. burnetii infectivity in milk (Combiescu et al .…”
Section: Properties Of the Coxiella Burnetii Organism With Relevance mentioning
confidence: 99%
“…Macrophages occur in bovine milk (Paape et al 2003). Within the macrophage, a high-density mixture of LCVs and SCVs exists in the parasitophorous vacuole (Minnick and Raghavan 2011). The LCV is very fragile (Minnick and Raghavan 2011).…”
Section: The Unit Of Coxiella Burnetii Infectivity In Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Its causal agent remained enigmatic for a brief period, then was identified and named C. burnetii [ 1 ]. Based on recent phylogenetic studies, this agent was found to be closely related to Legionella and no longer regarded as Rickettsia [ 2 ]. In addition to man, C. burnetii is adapted to several animal species primarily including sheep and goats.…”
Section: Introductionmentioning
confidence: 99%
“…However, some missing genes appear to be important in contemporary pathogen–host relationships, indicating functional redundancies. For example, ankyrin repeat domains may be involved with ensuring a stable replication niche during infections (Voth et al 2009), LuxR—family regulators thought to control growth within a host (Minnick and Raghavan 2011) and OmpA-like transmembrane domain proteins known to be immunoreactive (Beare et al 2008). Although the genes missing from different clades vary (Fig.…”
Section: Resultsmentioning
confidence: 99%